A wedding on Lilac Lane : a Moonlight Bay novel - Ramsay, Hope (Ramsay, Hope. Moonlight Bay series., 2021)
Determined to sabotage his father's upcoming nuptials to musician Ella McMillan's mother, Dr. Dylan Killough has a change of heart when he falls for Ella and must convince her that he really does believe in happily ever after.